Training of future biology teachers to organize excursions in school - Hrytsai, Nataliia; Trokhymchuk, Iryna; Grygus, Igor; Zukow, Walery (Journal of Education, Health and Sport, 2019)
Excursions are an important form of organization of teaching biology in secondary schools. However, in the universities, the methodical training of future biology teachers is more aimed at conducting lessons. In the article the necessity of goal-directed training of future teachers of Biology to organize excursions to nature (hikes) is substantiated, the real status of using excursions at the school practice is analyzed.